The prevalence of stalking among finnish university students - Björklund, K.; Häkkänen-Nyholm, H.; Sheridan, Lorraine; Roberts, K. (Sage Publications, 2010)
The present study examined the prevalence and nature of stalking among university students in Finland. The prevalence of stalking was analyzed in relation to stalking episodes, violent stalking victimization, the stalker-victim relationship, and stalking duration. A group of Finnish university students were contacted by e-mail and asked to participate in a stalking survey. In total, 615 students participated. Almost one fourth of the respondents (22.3%) had experienced one episode (i.e., period of time) of stalking, and more than one fourth (26.2%) reported being stalked two or more episodes (i.e., periods of time) in their lifetime. More than half (55%) of the stalkers were acquaintances, 25% were ex-partners, and 19% were strangers. The mean duration of stalking was 10 months. Stalking duration was significantly associated with stalker gender and prior victim-stalker relationship. Almost half of those being stalked (46%) had been exposed to violent or threatening behavior. Ex-partner stalkers were most likely to use violence as well as a wide range of violent stalking methods. Logistic regression analysis revealed significant independent associations between stalking violence and stalking behaviors. Stalking is highly prevalent among Finnish university students; it is maintained, on average, for a relatively long period; and it often includes some form of violence and/or threats. The results suggest that health care professionals require screening methods and schooling concerning stalking. © 2010 The Author(s).